Peran Mahasiswa KKN UINSU 2025 dalam Pemberdayaan Desa Pahang melalui Program Keagamaan, Kebersihan, dan Ekonomi Masyarakat - Aditya Dwipa Alkanzu; Fikry Haikal; Khairunnisa Khairunnisa; Reza Andhika Pramana; Imsar Imsar (Lembaga Pengembangan Kinerja Dosen, 2025)
Community Service (KKN) is part of the Tri Dharma of Higher Education, focusing on community service. This study aims to describe the role of KKN students from the State Islamic University of North Sumatra (UINSU) in 2025 in empowering the community of Pahang Village, Talawi District, Batubara Regency through a synergy of religious programs, collective hygiene, and economic empowerment. The method used was a qualitative descriptive approach with observation, interviews, and documentation techniques. The results of the activities indicate that students made a significant contribution to improving the community's religious literacy through religious studies, Quranic guidance, and strengthening village religious institutions. In terms of cleanliness, students successfully built collective awareness among residents through the Clean Friday program and waste management education. Meanwhile, in the economic sector, business skills training and mentoring of local MSMEs were able to encourage economic growth based on village potential. The synergy between the programs demonstrated high effectiveness in creating sustainable empowerment. This study concludes that the multidimensional integration of KKN student real work programs can be an effective strategy in building a religious, healthy, and economically independent village.